2000
DOI: 10.1042/bj3500579
|View full text |Cite
|
Sign up to set email alerts
|

A role for serine-175 in modulating the molecular conformation of calponin

Abstract: Calponin is an actin filament-associated protein found in smooth muscle and non-muscle cells. Calponin inhibits actin-myosin interaction in a manner that is prevented by protein kinase C (PKC)-catalysed phosphorylation of serine-175. To investigate the molecular basis of serine-175-mediated regulation, we examined the effect of phosphorylation on the conformation of calponin using monoclonal antibody (mAb) epitope analysis. Eight mAbs against different epitopes on chicken gizzard calponin were developed to mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Although the fusion protein contained aa 92-298, it included the putative phosphorylation site (Ser 175 ) (21). The fusion protein could also be identified by anticalponin monoclonal antibody, indicating that the expressed fusion protein was functional.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fusion protein contained aa 92-298, it included the putative phosphorylation site (Ser 175 ) (21). The fusion protein could also be identified by anticalponin monoclonal antibody, indicating that the expressed fusion protein was functional.…”
Section: Discussionmentioning
confidence: 99%
“…mAbs provide reagents for recognizing specific epitopes and can be used in monitoring protein conformation, structural dynamics, and folding (18). We have applied antibody probes against epitopes in allosteric proteins to detect conformational differences and changes using high throughput microtiter plate ELISA under native conditions (23,24,27,39).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that phosphoryltation of calponin decreases the binding affinity for F-actin (39). On the other hand, the observation that phosphorylated calponin was hardly detectable in living cells (40) may implicate that phosphorylation-induced calponin dissociation from the actin filaments is coupled with rapid degradation.…”
Section: Mechanical Tension Regulates H2-calponin By Controlling Bothmentioning
confidence: 99%